KELAYAKAN ISI DAN BAHASA PADA BUKU TEKS BAHASA INDONESIA DI SMA NEGERI 1 SIRAMPOG - Irma, Cintya Nurika (University of Brawijaya, 2022)
This study aims to determine the appropriateness of the content and language of the Indonesian language textbook for class XI SMA Negeri 1 Sirampog. The feasibility of the book is seen from the content and language components in accordance with the National Education Standards Agency (BNSP). This study used a qualitative method with a case study approach model, while the data collection in this study was carried out using a purposive technique. Furthermore, data validity was carried out by triangulating data sources and theories. The results showed that the feasibility of the content aspect obtained a percentage of 90, 86% and the feasibility of the language aspect obtained a percentage of 93% so it is classified as a very feasible book.